A análise da precisão do traçado de previsão manual nas rotações do complexo maxilo-mandibular em cirurgia ortognáticas bimaxilares - Lopes Filho, Antonio Mont`Alverne (2011)
Orthognathic surgery is the procedure of repositioning the jaws for the treatment of dentofacial deformities. For an optimal final result, correct diagnosis and planning is necessary. The surgery must reproduce with precision, what was planned in the predictive tracing. For some years, to obtain a functional and primarily satisfactory result, rotation of the maxillomandibular complex has been used. The objective of this retrospective study was to evaluate if the results obtained with orthognathic surgery, rotation of the maxillomandibular complex, were reproduced with precision to what was planned in the prediction tracing. Fifteen patients (n=15), 7 men and 8 women, with a mean age of 27 years underwent pre- and immediate post-operative cephalometric radiographs. Three tracings were produced: initial, based on preoperative radiography, predictive (PT), and post-operative (POT) based on post-operative radiography. The POT was superimposed on PT, and the postoperative values were compared to the pre-operative ones. Seventeen cephalometric measurements were used for the evaluation, 9 being angular and 8 linear. A horizontal axis Y (SN-70) and a vertical axis X (perpendicular to Y, passing through the Sella point) were created, to evaluate vertical and anteriorposterior alterations, respectively. From the 17 values, 5 presented statistically significant difference (p<0.005) between the obtained values and those planned. They are 1-NA (p=0.001), 1-NB (p=0.007), IMPA (p=0.036), Occlusal Plane (p=0.018) and ENP-Y (p=0.002). The other references did not present statistically significant differences between the surgical result and what was planned by the predictive tracings.